2002
DOI: 10.1002/imhj.10014
|View full text |Cite
|
Sign up to set email alerts
|

Early Head Start MAP: Manualized Assessment of Progress

Abstract: We present the Early Head Start MAP (Manualized Assessment of Progress) system, a newly developed program evaluation protocol for Early Head Start (EHS). Briefly, EHS is a prevention program for low-income families with infants, toddlers, and pregnant women. The EHS MAP protocol was designed to be incorporated into the fabric of the EHS program, utilized by all EHS staff members with input from EHS families. As such, it serves to document ongoing progress of children and families while enrolled in the program,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…These are central questions of the national implementation study and are addressed in reports released and yet to be released (DHHS, 1999a(DHHS, , 1999b(DHHS, , 2000. In addition, two studies reported in this issue address this topic (Dickstein, Seifer, Eguia, Kuersten-Hogan, & Magee, 2002;Paulsell et al, 2002). Programs seek to be responsive to changing family needs, but what happens to the staff when programs must change their service delivery models?…”
Section: Learning More About Program Qualitymentioning
confidence: 99%
“…These are central questions of the national implementation study and are addressed in reports released and yet to be released (DHHS, 1999a(DHHS, , 1999b(DHHS, , 2000. In addition, two studies reported in this issue address this topic (Dickstein, Seifer, Eguia, Kuersten-Hogan, & Magee, 2002;Paulsell et al, 2002). Programs seek to be responsive to changing family needs, but what happens to the staff when programs must change their service delivery models?…”
Section: Learning More About Program Qualitymentioning
confidence: 99%